Hantavirus: an infectious cause of acute kidney injury in the UK. (17th July 2014) - Adams, Kate; Jameson, Lisa; Meigh, Rolf; Brooks, Tim
Abstract : We present a case of an undifferentiated febrile illness in a 59-year-old man from East Yorkshire. He was initially treated for leptospirosis due to the fact that he had farm exposure and the findings of acute kidney injury (AKI), thrombocytopenia and a raised alanine transferase (ALT) on his initial blood results. Serology tests later proved him to have had another rodent-borne illness: hantavirus. An investigation by Public Health England (formerly known as Health Protection Agency) (PHE) went on to prove the presence of the same serotype of hantavirus in rats caught on the patient's property. After an initial deterioration, the patient made a relatively uneventful recovery and all his blood tests returned to normal levels.